Artificial Empathy: User Experiences with Emotionally Intelligent Chatbots - Rostami, Mehdi; Navabinejad, Shokouh (AI and Tech in Behavioral and Social Sciences, 2023)
This study aims to explore user experiences with emotionally intelligent chatbots, focusing on their perceived empathy, satisfaction with interactions, and the impact on user perception. Additionally, it seeks to identify the main challenges and future expectations users have towards these AI systems. Employing a qualitative research design, this study collected data through semi-structured interviews with 28 participants who had interacted with emotionally intelligent chatbots in various contexts. Thematic analysis was conducted to identify main themes, categories, and concepts within the data, providing insights into users' perceptions and experiences. The analysis revealed eight main themes: Perceived Empathy, Interaction Satisfaction, Trust and Security, Human-Like Interaction, User Adaptation, Impact on User Perception, Barriers to Engagement, and Future Expectations. These themes encompass categories such as Emotional Understanding, Contextual Sensitivity, Engagement Level, Privacy Concerns, Learning Curve, AI Capabilities, Technological Limitations, and Improvement Suggestions. Participants valued chatbots' ability to understand and adapt to their emotional states but highlighted challenges in achieving authentic empathy and expressed concerns over privacy and data security. Emotionally intelligent chatbots hold promise for enhancing user experiences through artificial empathy. However, the authenticity of empathy, coupled with ethical considerations such as privacy and security, presents significant challenges. Future developments should focus on improving the genuineness of empathetic responses, ensuring ethical use of AI, and addressing users' concerns to fully realize the potential of emotionally intelligent chatbots.